Evaluasi Program Pemberian Makanan Tambahan Pemulihan (PMT-P) terhadap Status Gizi Buruk Balita di Puskesmas Oepoi Kota Kupang - Wihelmus Kopong Doren; Tadeus A. L. Regaletha; Dominirsep O. Dodo (Lontar : Journal of Community Health, 2019)
Toddlers are the group most vulnerable to experiencing nutritional problems, especially malnutrition problems such as thin, short, and malnutrition. Malnutrition in children also affects the cognitive abilities and intelligence of children. Malnutrition casse always found in the Oepoi Health Center from 2016-2018. In 2016 there were 124 people, in 2017 there were 88 people and in 2018 there were 46 people. The program to reduce malnutrition, namely PMT-P, nutritional supplementation in the form of food additives in the form of biscuits with special formulations and fortified with vitamins and minerals given to infants and toddlers aged 6-59 months with thin category. This study aims to evaluate the implementation of supplementary feeding programs for the recovery of the nutritional status of children under five in the working area of Kupang City Oepoi Health Center in terms of Input, Process and Output aspects. This type of research is descriptive with 6 research informants. The results showed that: input for the number of malnutrition workers, Puskesmas needed 1 community health worker, lack of equipment in the laboratory section had to ask for procurement from the City or Provincial Health Office and funds for MT distribution were not yet available, the planning process was good but the implementation was good from distribution, monitoring and recording / reporting, there are still problems with monitoring because it is found that there are other family members eating MT packages, the outputs are not on target and the program coverage also has not reached the specified performance indicators. Suggestions for the government of the City of Kupang, especially the Health Office of the City of Kupang to provide facilities and infrastructure that is lacking at the health center, while for the Oepoi Community Health Center should provide counseling about the importance of PMT-P so that the MT given on target.